Genetic and genomic analyses of tree architectural traits in Hevea brasiliensis revealed genes underlying QTLs linked to key developmental processes - Nur Eko Prasetyo; David Lopez; Fetrina Oktavia; Eka Tarwaca Susila Putra; Pascal Montoro (PLoS ONE, 2026)
The architectural characteristics of rubber trees are increasingly important in the context of climate change. Branching, canopy shape and growth pattern have to be adapted to monocropping and intercropping systems to foster latex and wood production, wind-tolerance, light availability and microclimate for intercrops, and soil stability and fertility. This study aimed to identify key architectural traits that could be used in breeding programs as well as chromosomal regions underlying QTLs that could be targeted for marker-assisted selection. Five quantitative (height of bole, trunk girth, estimated bole volume, number of terminal branches and apical shoots) and five qualitative (tree straightness, axillary shoot score, type of crown and axillary shoot, diameter of axillary shoot) architectural traits were phenotyped in a segregating population derived from clones PB 260 and SP 217. The frequencies of categories for each qualitative architectural variable were analysed as quantitative variables. A principal component analysis performed with these traits showed that trunk girth, estimated bole volume, round crown and medium diameter of axillary branches are negatively correlated with small diameter of axillary branches and conical type of crown. Seven architectural variables have heritability greater than 0.50. Twenty quantitative trait loci and their underlying genes and functions were pinpointed using the high-density genetic map previously constructed and an improved high-quality genome of the parent clone PB 260. Of the 680 genes found in chromosomal regions under QTLs, 19 genes have a function directly involved in plant development such as transcription factors related to the regulation of shoot apical meristem (SAM) and vascular cambium activity (WUSCHEL). A literature review was also conducted to provide additional insights into tree architecture and its impacts on agricultural systems. This first genetic analysis of architectural traits in rubber revealed that seven traits (trunk girth, bole height, estimated bole volume, number of apical branches, diameter of axillary branches, number of terminal branches and type of crown) could play a major role in rubber breeding both for monoculture and agroforestry single and double row systems. Chromosomal regions harbouring developmental genes could be used to develop specific strategy of marker-assisted selection.